Implementasi Nilai Kepemimpinan Nabi Muhammad Saw. dalam Pendidikan Islam: Kajian Kitab Nūrul Mubīn - Baskara, Renaldi Habib; Sopingi, Imam; Hidayati, Athi’ (Ahdāf: Jurnal Pendidikan Agama Islam, 2025)
The prophetic leadership of Prophet Muhammad (peace be upon him) has long served as an ethical reference in Islamic tradition; however, studies on its relevance to Islamic education in Indonesia remain limited. Nūrul Mubīn fī Maḥabbati Sayyidil Mursalīn by KH. Hasyim Asy‘ari presents a concise narrative of the Prophet’s life while articulating leadership values with strong potential for revitalization within educational contexts. This study employs a qualitative approach using the library research method. Data were drawn from the primary text Nūrul Mubīn and other classical works such as Sīrah Nabawiyyah and Al-Raheeq al-Makhtum, then analysed comparatively and hermeneutically to identify the relevance of prophetic leadership values in contemporary Islamic education. The findings reveal that Nūrul Mubīn emphasizes three core dimensions of the Prophet’s leadership: moral integrity (ṣidq, amānah), social empathy (khādim al-ummah), and pedagogical exemplarity (murabbī al-ummah). Compared with other classical texts, KH. Hasyim Asy‘ari’s work stands out for its normative, spiritual, and educational orientation, which can be directly integrated into educational practice. These values are profoundly relevant in addressing issues such as integrity crises, weak character education, and leadership challenges in Indonesia’s education sector. Nūrul Mubīn makes a significant contribution to the revitalization of prophetic-based Islamic education in Indonesia. The text offers a leadership paradigm grounded in moral virtue, justice, and compassion, applicable to curriculum development, teaching strategies, and institutional management in Islamic education. The study’s implications open pathways for further research on integrating prophetic values into educational praxis to cultivate a generation that is intellectually grounded, morally upright, and socially responsible.